Fabrication of n-type CuInS2 modified TiO2 nanotube arrays heterostructure photoelectrode with enhanced photoelectrocatalytic properties - Li, T.; Li, Xin Yong; Zhao, Q.; Shi, Y.; Teng, W. (Elsevier, 2014)
A novel n-type CuInS2 modified TiO2 nanotube arrays (NTs) heterostructure photoelectrode was successfully prepared via an ultrasonication-assisted cathodic electrodeposition strategy. CuInS2 particles were uniformly decorated on the inner and external walls of the TiO2 NTs electrode. The stoichiometry measured by XPS and ICP-OES clearly illustrated the excess indium. Mott–Schottky analysis further demonstrated CuInS2 possessed an n-type feature. Optical characterizations indicated that the introduced CuInS2 could extend the visible-light response range and enhance the visible light photoactivity. Moreover, the electrochemical measurements attested to a significant improvement of the interfacial electron-transfer properties. The photoelectrocatalytic (PEC) activity of CuInS2/TiO2 NTs electrode was evaluated by degradation of 2-chlorophenol (2-CP) under visible light irradiation (λ > 420 nm). The results indicated that the as-prepared CuInS2/TiO2 NTs electrode displayed much higher PEC performance than that of the pure TiO2 NTs electrode.